Seven Theses on Spanish Justice to understand the Prosecution of Judge Garzón - Joxerramon Bengoetxea (Oñati Socio-Legal Series)
Judges may not decide cases as they wish, they are subject to the law they are entrusted to apply, a law made by the legislator (heteronomy). But in doing so, they do not take any instruction from any other power or instance (independence or autonomy). Sometimes, they apply the law of the land taking into account the norms and principles of other, international, supranational, even transnational systems. In such cases, again, they perform a delicate balance between autonomy (domestic legal order and domestic culture of legal interpretation) and heteronomy (external legal order and culture of interpretation). There are common shared aspects of Justice in the Member States of the EU, but, this contribution explores some, perhaps the most salient, features of Spanish Justice in this wider European context. They are not exclusive to Spain, but they way they combine and interact, and their intensity is quite uniquely Spanish. These are seven theses about Justice in Spain.